Effect of Host Generation on the Luminescent and Charge Transporting Properties of Solution Processed OLEDs. Issue 20 (29th September 2021) - Gao, Mile; Jang, Junhyuk; Leitner, Tanja; Mai, Van T. N.; Ranasinghe, Chandana S. K.; Chu, Ronan; Burn, Paul L.; Pivrikas, Almantas; Shaw, Paul E.
Abstract: Tris(4‐carbazoyl‐9‐ylphenyl)amine (TCTA) is a commonly used host material for organic light‐emitting diodes (OLEDs). TCTA has poor solubility and hence to improve solubility the authors have synthesized first‐ and second‐generation TCTA‐based dendrimers with n ‐propyl surface groups. These dendrimeric TCTA hosts have improved solubility and similar photophysical properties to TCTA. The hole mobility of solution‐processed TCTA is found to be an order of magnitude less than films formed by evaporation and similar to that of the two dendronized TCTAs (mobilities in the order of 10 −5  cm 2  V −1  s −1 ). The hole mobility in the films is found to decrease when a green emissive first‐generation light‐emitting dendrimer is blended with the host materials due to charge trapping on the emissive guest. In the case of the second‐generation host, there is evidence of a degree of phase separation in the film. Organic light‐emitting diodes are fabricated at guest concentrations corresponding to the maximum observed photoluminescence quantum yield (PLQY) and lowest hole mobility. It is found that the external quantum efficiency (EQE) does not always scale with the PLQY, leading to devices that have EQEs higher than expected based on the PLQY and outcoupling of light from a bottom emitting device. Abstract : Energy transfer, photoluminescence quantum yield (PLQY), charge mobility, and organic light‐emitting diode (OLED) performance are found to be dependent on the generation of the dendrimer host. OLED performance of the TCTA‐based host materials blended with a soluble phosphorescent light‐emitting dendrimer is found to depend on the maximum film PLQY, with good external quantum efficiencies achieved despite low charge mobilities.